Paradoxical granulomatous reaction to ustekinumab - Chinemelum Obijiofor; Daniel R. Mazori; Alisa N. Femia; Alexandra Flamm; Avrom S. Caplan (Wiley, 2024)
Abstract Sarcoidosis is a multisystem disorder characterised by granulomatous inflammation affecting various organs. The skin is commonly involved and can serve as an initial indicator of disease. While the precise aetiology of sarcoidosis remains elusive, evidence suggests involvement of T‐helper type (TH)‐1 and TH‐17 pathways. Psoriasis shares common inflammatory pathways with sarcoidosis, prompting the repurposing of biologic therapies approved for psoriasis for off‐label treatment of cutaneous sarcoidosis. However, this approach has raised concerns due to the development of granulomatous eruptions in some patients. We present a case of a patient with psoriasis who was diagnosed with systemic sarcoidosis while on ustekinumab. We review previous cases of ustekinumab‐associated sarcoidosis and discuss the challenges associated with utilising biologic agents originally intended for psoriasis treatment for sarcoidosis.